Indonesian Tourism Discourse on www.indonesia.travel: Mood Analysis - Arina Isti'anah (Langkawi: Journal of The Association for Arabic and English, 2020)
Tourism is an important topic to observe since it affects a country’s economic vibrancy and global image. Scholars have researched the tourism website's lexical and visual features, yet none observed how the website builds an interpersonal relationship to the browsers. Thus, this paper sheds light on how Indonesian tourism website exchanges information, goods, and services to the browsers. Two problems are addressed in this paper: (1) how are the mood structures employed on the Indonesian tourism website? (2) what are tourism discourses revealed on the web? To answer them, ten sample articles of Medan, Raja Ampat, Bali, Banyuwangi, Jakarta, Yogyakarta, Bandung, Makassar, Lombok, and Wakatobi highlighted on the front page of the website, accessed on www.indonesia.travel, were analyzed through Discourse Analysis approach. The 461 collected clauses were categorized into the mood structures and their speech functions. The results showed that the website was dominated by declarative mood functioning as statements, seen in 328 clauses, or 71.6% of the total clauses. It implied that promotion was not thoroughly involved, proven by the limited number of the speech function “offer”. The website's mood structures aimed to present itineraries and access, a place to play, and authenticity. Aside from culinary and cultural heritage, the website also presented traditional transportation and game as Indonesian authenticity. The commodity given on the website was in the form of information to help the prospective tourists prepare for their trip to Indonesia.